Catching up of emerging economies: the role of capital goods imports, FDI inflows, domestic investment and absorptive capacity. Issue 2 (22nd January 2016) - Glas, Alexander; Hübler, Michael; Nunnenkamp, Peter
Abstract: We show that the impact of capital goods imports and FDI inflows on economic convergence depends on the local capacity of emerging economies to absorb superior technologies.